2007
DOI: 10.1093/bioinformatics/btm309
|View full text |Cite
|
Sign up to set email alerts
|

Systematic construction of gene coexpression networks with applications to human T helper cell differentiation process

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 30 publications
0
102
0
1
Order By: Relevance
“…Previous DN analytical studies usually considered a single network feature to identify genes that show important changes in two networks (Choi et al, 2005;Elo et al, 2007;Fuller et al, 2007;Yu et al, 2011). However, whether a single feature is sufficient to detect all of the genes of interest remains unevaluated, considering that genes with different functional roles might have different connection patterns with other genes in a network.…”
Section: Multiple Features Versus a Single Feature For Dn Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Previous DN analytical studies usually considered a single network feature to identify genes that show important changes in two networks (Choi et al, 2005;Elo et al, 2007;Fuller et al, 2007;Yu et al, 2011). However, whether a single feature is sufficient to detect all of the genes of interest remains unevaluated, considering that genes with different functional roles might have different connection patterns with other genes in a network.…”
Section: Multiple Features Versus a Single Feature For Dn Analysismentioning
confidence: 99%
“…Among the network analytical techniques that have recently been applied in biology, differential network (DN) analysis has shown robustness, which is evident in its ability to identify the DNA damage response genes in yeast (Bandyopadhyay et al, 2010;Califano, 2011), body weight-related genes in mice (Fuller et al, 2007;Gill et al, 2010), T cell differentiation-related genes in human (Elo et al, 2007), and human disease-relevant genes (Hudson et al, 2009;Amar et al, 2013). In contrast with DE analysis, which is a gene-centric analytic approach that assesses expression changes in individual genes, DN analysis is a networkcentric analytic approach that focuses on detecting the changes in a gene's associations with other genes via a comparison of two or more networks that were constructed under different experimental conditions (de la Fuente, 2010;Hudson et al, 2012;Ideker and Krogan, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aoki et al (2007) showed that the Arabidopsis coexpression network had a minimal network density at a cutoff r value ranging from 0.55 to 0.60. Using simulated data sets, Elo et al (2007) demonstrated that a cutoff value of r = 0.6 yielded both low error and high reproducibility.…”
Section: Discussionmentioning
confidence: 99%